Sawahlunto Sang Penghasil Bahan Bakar: Mungkinkah Abadi? - Goembira, Fadjar (Puitika, 2024)
Based on a report by Van Lier (1917), it was written that the Sawahlunto community had utilized coal exposed to the surface as fuel for cooking long before the exploitation and exploration activities by the Dutch East Indies Government. The term used for the coal was charcoal tongue (daagzoom), and the community used boats on the Ombilin River to sell the commodity to South Sawahlunto. Based on historical records from PT Bukit Asam, an entity that was once the largest coal mine manager in Sawahlunto in the era of independence, the species and utilization of coal increased significantly after the discovery of coal reserves around the Ombilin River, as much as 205 million tons by Willem Hendrik de Greve in 1867. Pioneering mining was carried out by the Dutch East Indies Government in 1876 and began operating in 1891, with production records in 1892 of 48 thousand tons and peak production in 1995 of 1.2 million tons based on data from PT Bukit Asam. Of the many mining business permits (IUP) managed by several companies, both state-owned and private, several former mining areas have been appropriately reclaimed and become tourist areas. However, some former mining areas need to be appropriately managed and have turned into critical land. On the other hand, there are several mining company assets that are currently not being utilized, as well as the Ombilin Steam Power Plant (PLTU), which is still operating using coal fuel. Is it possible to utilize critical former mining areas to plant energy crops whose harvests can be processed in such a way by a business unit into renewable fuels to be used as alternative fuels, for example, by a power plant? By doing so, it is hoped that Sawahlunto, which has long been known as a fuel producer, can maintain its status as a Fuel Producer. This article will present this potential, including stakeholders who can be involved in realizing it.